If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -11 = x + 11 Reorder the terms: -11 + x = x + 11 Reorder the terms: -11 + x = 11 + x Add '-1x' to each side of the equation. -11 + x + -1x = 11 + x + -1x Combine like terms: x + -1x = 0 -11 + 0 = 11 + x + -1x -11 = 11 + x + -1x Combine like terms: x + -1x = 0 -11 = 11 + 0 -11 = 11 Solving -11 = 11 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 13+v=3 | | 18-n=17 | | -20-p=-11 | | (1/6)/(1/2) | | 6(2x-6)=6(4-x) | | p+15=0 | | 1/6/1/2 | | 5.6*10= | | -8-k=-12 | | -3-m=9 | | x^2+15x=-54 | | -20+k=-31 | | 17-5+x=5+9-1 | | 1/4(10x-5)=4 | | -16+b=-13 | | Log(x+1)+log(x-1)=log(x+1) | | 9+m=12 | | 22/25.15/52.8/33 | | y=-1(2)-2 | | y=-1(1)-2 | | y+(2)=-6 | | y+(-6)=-6 | | x-7.3=-5.7 | | 7+24/2*5-9= | | 2(5)+y=10 | | 13x-35=5x+1 | | 2(2)+y=10 | | 16+(-20)= | | y=2(9)-9 | | x^2=-640 | | 4(3x+5)-8x=14+16x | | y=2(2)-9 |